Transformation of the Personnel Policy of Russian Universities Participating in Project 5-100: The Case of National Research Nuclear University Mephi - E. A. Drugova; I. B. Pleshkevich; T. V. Klimova (Высшее образование в России)
The article examines the development of personnel policy and human resource management (HRM) in Russian universities under the influence of the Project 5-100. Globalization has intensified the processes of universities corporatization and the spread of effective management practices. National academic excellence programs have contributed to strengthening the performance-based governance in universities all over the world. These factors had deeply influenced the transformation of HRM practices at universities. Russian studies in this field are shown as fragmented, focusing on narrow aspects, and not forming a holistic picture of the HRM system transformation in Russian universities. This work aims to describe a holistic case of personnel policy and HRM system development in one of the leading Russian universities – the National Research Nuclear University “MEPhI” (Moscow Engineering Physics Institute).The research applied the method of semi-formalized interviews and covered 25 employees of MEPhI. Four interview guides were developed for different categories of employees (top management, middle management, academics, teachers), including more than 25 questions, focusing on employees’ perception of different components of the HRM system at the university. The study showed that the HRM system at MEPhI was significantly transformed under the influence of the Project 5-100: the personnel policy was formalized in high-level strategic documents; the processes of recruitment and selection of foreign employees have been rebuilt; the considerable increase in the number of foreign employees was reached; global partners began to play an important role; a comfortable environment for the implementation of initiatives was created and opportunities for professional development were provided. A significant part of these changes is connected, directly or indirectly, with the university’s participation in the Project 5-100. In general, this points to its positive impact on personnel policy and the HRM system at the university. The results obtained can be used as a basis for formulating recommendations for improving the personnel policy and HRM system in Russian universities as an important component of the management system as a whole.